2022
DOI: 10.3389/fphar.2021.808480
|View full text |Cite
|
Sign up to set email alerts
|

Fisetin Attenuates Doxorubicin-Induced Cardiomyopathy In Vivo and In Vitro by Inhibiting Ferroptosis Through SIRT1/Nrf2 Signaling Pathway Activation

Abstract: Doxorubicin (DOX) is an anthracycline antibiotic that is used extensively for the management of carcinoma; however, its clinical application is limited due to its serious cardiotoxic side effects. Ferroptosis represents iron-dependent and reactive oxygen species (ROS)-related cell death and has been proven to contribute to the progression of DOX-induced cardiomyopathy. Fisetin is a natural flavonoid that is abundantly present in fruits and vegetables. It has been reported to exert cardioprotective effects agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
76
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(91 citation statements)
references
References 79 publications
(106 reference statements)
15
76
0
Order By: Relevance
“…Our results showed that fisetin remarkably enhanced the expression and phosphorylation of Nrf2 as well as its expression in the nucleus in H 2 O 2 -treated ARPE-19 cells. Fisetin also improved the expression and enzymatic activity of HO-1, suggesting that fisetin was able to activate the Nrf2/AREs pathway, which was in good agreement with previous findings ( Hanneken et al, 2006 ; Sim et al, 2020 ; Jiang et al, 2021 ; Li et al, 2022 ). However, the ROS scavenging activity and viability-enhancing ability of fisetin were significantly abolished by blocking HO-1 activity via a HO-1 antagonist ZnPP.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results showed that fisetin remarkably enhanced the expression and phosphorylation of Nrf2 as well as its expression in the nucleus in H 2 O 2 -treated ARPE-19 cells. Fisetin also improved the expression and enzymatic activity of HO-1, suggesting that fisetin was able to activate the Nrf2/AREs pathway, which was in good agreement with previous findings ( Hanneken et al, 2006 ; Sim et al, 2020 ; Jiang et al, 2021 ; Li et al, 2022 ). However, the ROS scavenging activity and viability-enhancing ability of fisetin were significantly abolished by blocking HO-1 activity via a HO-1 antagonist ZnPP.…”
Section: Discussionsupporting
confidence: 92%
“…Certain intracellular signaling pathways are involved in defense strategies against oxidative stress, and there is growing evidence that the Nrf2/AREs pathway is involved in the antioxidant activity of fisetin in multiple cell lines ( Sim et al, 2020 ; Jiang et al, 2021 ; Li et al, 2022 ). There is growing evidence that Nrf2 is an effective target in the regulation of oxidative stress-related retinal degeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies showed that fisetin protects against DOX-induced cardiomyopathy by inhibiting ferroptosis via SIRT1/Nrf2 signaling pathway activation. 103 Salidroside, an extraction from traditional Chinese medicine Rhodiola rosea, also significantly attenuated ferroptosis and fibrosis in a mice model of DIC. However, the molecular mechanism is different; the antiferroptotic effects of salidroside are mediated by activating AMPK-dependent signaling pathways including regulating abnormal fatty acid metabolism and maintaining mitochondrial function.…”
Section: Dovepressmentioning
confidence: 98%
“…In addition, Nrf2 can be activated by deacetylation of SIRT1, and Fisetin activated Nrf2 by up-regulating the expression of SIRT1, leading to the up-regulation of HO-1, FTH1, TfR1, and FPN, and exerting an anti-ferroptosis effect. After being transfected with SIRT1 and Nrf2 siRNA, the anti-ferroptosis effect of Fisetin was abolished in H9C2 cells ( 105 ).…”
Section: Ferroptosis and Anthracycline-induced Cardiotoxicitymentioning
confidence: 99%